Bis(perchlorocatecholato)germane: Hard and Soft Lewis Superacid with Unlimited Water Stability. Issue 47 (11th September 2020) - Roth, Daniel; Wadepohl, Hubert; Greb, Lutz
Abstract: Previously described Lewis superacids are moisture sensitive and predominantly hard in character—features that severely limit their widespread use in orbital‐controlled reactions and under non‐inert conditions. Described here are adducts of bis(perchlorocatecholato)germane, the first hard and soft Lewis superacid based on germanium. Remarkably, the synthesis of this compound is performed in water, and the obtained H2 O adduct constitutes a strong Brønsted acid. If applied as an adduct with aprotic donors, it displays excellent activity in a diverse set of Lewis acid catalyzed transformations, covering hydrosilylation, hydrodefluorination, transfer hydrogenation, and carbonyl–olefin metathesis. Given the very straightforward synthetic access from two commercially available precursors, the unlimited water stability and the soft Lewis acidic character, it promotes the transfer of Lewis superacidity into organic synthesis and materials science. Abstract : Bis(perchlorocatecholato)germane is a hard and soft Lewis superacid with unlimited water stability. Its utility in catalysis as both a Lewis and Brønsted acid was demonstrated by application to a variety of catalytic transformations, such as hydrodefluorination, hydrosilylation, transfer hydrogenation, and carbonyl–olefin metathesis.